The role of monitoring of technical condition of magistral oil pumping ways in the system of prevention and liquidation of emergency situations - Shil’ko С. В.; Kuz’minskiy Ю. Г. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
For the prediction and overcome incidents which is caused by oil transportation, the monitoring of pipe’s state has been analyzing and adaptive control system «monitoring-computer model-operator-device» based on primary information sources, stress-strained and hydrodynamics modeling as well as automatic information systems has been discussed.